Research services - Chapman, Liz (Henry Stewart Talks, 2012)
Research Library context, Constraints and changes, Changes in role, Where is the digital library?, Researchers' constraints and changes, Researchers' needs, Support for researchers, Publications, Preservation, Strategic vision, Staff, Services, Visibility, Background reading